Heat exchange membrane with efficient moisture permeability as well as preparation method and application of heat exchange membrane

By combining the support membrane with the porous polymer membrane and applying a hydrophilic coating on both sides of the porous base membrane, the problem of the prone to bacterial growth and insufficient moisture permeability of traditional heat exchange membrane materials is solved, and a heat exchange membrane with efficient moisture permeability and airtightness is achieved, meeting the needs of a full heat exchange core.

CN119798771APending Publication Date: 2025-04-11NANJING FIBERGLASS RES & DESIGN INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411917067.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional heat exchange membrane materials are prone to breed bacteria during long-term use, affecting air quality and equipment performance, and their moisture permeability is difficult to meet the needs of efficient heat exchange.

Method used

By combining the support film with the porous polymer film and applying hydrophilic coating slurry to both sides of the porous base film, an efficient moisture permeability path is formed to improve the airtightness and moisture permeability of the heat exchange membrane.

Benefits of technology

It achieves good airtightness, efficient moisture permeability and excellent anti-mold performance of the heat exchange membrane, and meets the high moisture permeability and airtightness of the heat exchange membrane of the high moisture permeability and airtightness of the heat exchange membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798771A_ABST
    Figure CN119798771A_ABST
Patent Text Reader

Abstract

The invention relates to a heat exchange membrane with efficient moisture permeability and a preparation method and application thereof, and belongs to the technical field of heat exchange.The preparation method of the heat exchange membrane with efficient moisture permeability comprises the steps that a supporting membrane and a porous base membrane are compounded; the porous base membrane is a porous polymer membrane, the pore diameter of the porous polymer membrane is 100-1500nm, and the porosity of the porous polymer membrane is 35-70%; the surface of the porous base membrane is coated with hydrophilic coating slurry, hydrophilic coatings are formed on the two faces of the porous base membrane through drying, and the heat exchange membrane with the efficient moisture permeability is obtained; a hydrophilic material in the hydrophilic coating slurry accounts for 15-40 wt%; the hydrophilic material is sulfonate. The heat exchange membrane provided by the invention has good air tightness, efficient moisture permeability and excellent mildew resistance, and can meet the use requirements of an efficient heat exchange total heat exchange core on high moisture permeability and air tightness of the heat exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat exchange, and in particular to a heat exchange membrane with high-efficiency moisture permeability, and a preparation method and application thereof. Background Art

[0002] With the advancement of science and technology and the improvement of people's requirements for quality of life, residents' awareness of healthy living environment has increased, and people's demand for healthy fresh air has surged. The total heat exchanger, as a typical healthy fresh air device, has been widely used in civil comfort occasions. Its principle is to transfer the "temperature" and "humidity" of the air exhausted from indoors to outdoors to the air supplied from outdoors to indoors, and return to indoors. The fresh air is purified by the filter of the total heat exchanger, and then the clean and comfortable fresh air is sent into the room after heat exchange with the indoor exhaust air (or return air) in the total heat exchange core, so as to supplement the fresh air in the indoor space, discharge the indoor dirty air, and adjust the temperature and humidity. It uses the indoor return air to pre-cool or pre-heat the fresh air, so that the energy that originally exists in the room but cannot be used can be used to the maximum extent, thereby reducing the energy consumption of the system.

[0003] As the core component of the fresh air system, the full heat exchange core is an important guarantee for delivering fresh air and creating a comfortable indoor environment. The full heat exchange core is mainly composed of a heat exchange membrane and a reinforcement body, among which the heat exchange membrane mainly plays the role of thermal conductivity, gas shielding and moisture permeability. However, traditional heat exchange membrane materials are prone to breeding bacteria during long-term use, affecting air quality and equipment performance. At the same time, its moisture permeability is difficult to meet the needs of efficient heat exchange. Summary of the invention

[0004] In response to one or more technical problems existing in the prior art, the present invention provides a heat exchange membrane with high-efficiency moisture permeability and a preparation method and application thereof. The heat exchange membrane provided by the present invention has good air tightness, high-efficiency moisture permeability and excellent mildew resistance, which can meet the use requirements of high-efficiency heat exchange and full heat exchange core for heat exchange membranes with high moisture permeability and air tightness.

[0005] In a first aspect, the present invention provides a method for preparing a heat exchange membrane with high-efficiency moisture permeability, the preparation method comprising:

[0006] Compounding the support membrane with a porous base membrane; the porous base membrane is a porous polymer membrane, the pore size of the porous polymer membrane is 100 to 1500 nm, and the porosity is 35 to 70%;

[0007] A hydrophilic coating slurry is coated on one side of the porous base membrane, and after drying, a hydrophilic coating is formed on both sides of the porous base membrane to obtain a heat exchange membrane with high efficiency moisture permeability; the hydrophilic material in the hydrophilic coating slurry accounts for 15-40wt%; the hydrophilic material is sulfonate.

[0008] Preferably, the porous polymer membrane is one of a porous PE membrane, a porous PTFE membrane, a porous PVDF membrane, and a porous PP membrane; and / or

[0009] The use temperature of the support film is greater than 100° C., and the support film is preferably a PET film.

[0010] Preferably, the composite method adopts a pressing and winding method; during the pressing and winding process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is controlled to be 0.5 to 2.5 m / s.

[0011] Preferably, the sulfonate is one or more of aminoalkyl sulfonate, sodium dodecylbenzene sulfonate, and biguanide trioctylbenzene sulfonate.

[0012] Preferably, the coating is performed by roller coating, and during the roller coating process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is controlled to be 0.3 to 0.8 m / s.

[0013] Preferably, the amount of the hydrophilic material is controlled to be 5 to 7 g / m 2 .

[0014] Preferably, the drying temperature is 95-100° C. and the drying time is 50-60 seconds.

[0015] Preferably, after the drying, a release and winding step is also included; during the release and winding process, the winding tension of the support film is greater than the winding tension of the heat exchange film; preferably, the winding tension of the support film is 2.5 to 4 kgf, and the winding tension of the heat exchange film is 0.5 to 1 kgf; and / or

[0016] During the release and winding process, the support film and the heat exchange film have the same winding speed; preferably, the support film and the heat exchange film have a winding speed of 0.5-1 m / s.

[0017] In a second aspect, the present invention further provides a heat exchange membrane with high-efficiency moisture permeability, which is prepared by the preparation method described in the first aspect.

[0018] The present invention further provides, in a third aspect, an application of the heat exchange membrane with high-efficiency moisture permeability as described in the second aspect, for use in a total heat exchange core.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] The present invention selects a porous polymer film with a certain pore structure as a base film, and coats a corresponding hydrophilic coating slurry on one side of the porous base film, so that the hydrophilic coating slurry can penetrate into the gaps of the porous base film and reach the other side of the porous base film. By coating both sides of the porous base film at one time to form a uniform hydrophilic coating and filling the pores of the porous base film with hydrophilic materials, the air tightness of the heat exchange can be effectively improved; the coatings on both sides of the porous base film are connected by the hydrophilic material filled in the pores to form an efficient moisture permeable passage, thereby improving the moisture permeability of the heat exchange membrane. The preparation method of the heat exchange membrane provided by the present invention can achieve double-sided hydrophilic coating at one time, with high coating efficiency and low cost, and can effectively solve the problems of low efficiency and high cost in forming double-sided coatings in the existing single-sided coating method.

[0021] The heat exchange membrane provided by the present invention has good air tightness, efficient moisture permeability and excellent mildew resistance, and can meet the use requirements of the high moisture permeability and air tightness of the heat exchange membrane for the efficient heat exchange full heat exchange core. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is a schematic diagram of the cross-sectional structure of the heat exchange membrane with high efficiency moisture permeability provided by the present invention.

[0024] Reference numerals: 11 - porous base membrane; 12 - hydrophilic coating layer. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] In a first aspect, the present invention provides a method for preparing a heat exchange membrane with high-efficiency moisture permeability, the preparation method comprising:

[0027] Compounding the support membrane with the porous base membrane 11; the porous base membrane 11 is a porous polymer membrane, the pore size of the porous polymer membrane is 100-1500nm (for example, it can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm or 1500nm), and the porosity is 35-70% (for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%);

[0028] A hydrophilic coating slurry is coated on one side of the porous base membrane, and after drying, a hydrophilic coating 12 is formed on both sides of the porous base membrane 11 to obtain a heat exchange membrane with high efficiency moisture permeability; the hydrophilic material in the hydrophilic coating slurry accounts for 15 to 40 wt% (for example, it can be 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt% or 40 wt%), preferably 20 to 40 wt%; the hydrophilic material is sulfonate.

[0029] The present invention selects a porous polymer film with a certain pore structure as a base film, and coats a corresponding hydrophilic coating slurry on one side of the porous base film, so that the hydrophilic coating slurry can penetrate into the gaps of the porous base film and reach the other side of the porous base film. By coating both sides of the porous base film at one time to form a uniform hydrophilic coating and filling the pores of the porous base film with hydrophilic materials, the air tightness of the heat exchange can be effectively improved; the coatings on both sides of the porous base film are connected by the hydrophilic material filled in the pores to form an efficient moisture permeable passage, thereby improving the moisture permeability of the heat exchange membrane. The preparation method of the heat exchange membrane provided by the present invention can achieve double-sided hydrophilic coating at one time, with high coating efficiency and low cost, and can effectively solve the problems of low efficiency and high cost in forming double-sided coatings in the existing single-sided coating method.

[0030] The heat exchange membrane provided by the present invention has good air tightness, efficient moisture permeability and excellent mildew resistance, and can meet the use requirements of the high moisture permeability and air tightness of the heat exchange membrane for the efficient heat exchange full heat exchange core.

[0031] The structure of the porous base film of the present invention (the distribution and size of the pores) and the concentration of the hydrophilic coating slurry jointly determine whether the hydrophilic coating slurry can penetrate into the pores of the porous base film and the other side of the base film, and form an effective hydrophilic coating on both sides of the base film to obtain a heat exchange membrane with moisture permeability. Based on this, the present invention selects a porous polymer film with uniform pore distribution, a pore size of 100 to 1500 nm, and a porosity of 35 to 70% as the base film. Under the condition of a certain base film, the concentration of the hydrophilic coating slurry (the content of the hydrophilic material in the hydrophilic coating slurry) is crucial. If the concentration is too low, an effective hydrophilic coating cannot be formed, and the moisture permeability of the porous polymer film is not greatly improved; if the concentration is too high, the hydrophilic material molecules may form aggregates or micellar structures, blocking the pores of the film, resulting in the slurry being unable to penetrate to the other side of the porous base film, and it is impossible to form a uniform hydrophilic coating on both sides of the base film at one time, which is also not conducive to the improvement of the moisture permeability of the porous polymer film.

[0032] According to some preferred embodiments, the porous polymer membrane is one of a porous PE membrane, a porous PTFE membrane, a porous PVDF membrane, and a porous PP membrane.

[0033] According to some preferred embodiments, the use temperature of the support film is greater than 100° C., and the support film is preferably a PET film.

[0034] Since the porous polymer film has poor overall high temperature resistance, it will shrink and deform at about 80-90°C, and the temperature at which the hydrophilic coating is completely dried is about 100°C. Therefore, the present invention will compound the porous polymer film with a support film having excellent physical and mechanical properties and a use temperature above 100°C by pressing and rolling before coating. The support film can effectively improve the problem of the porous polymer film being prone to heat shrinkage during the drying process through the support effect of the support film on the porous polymer film. The support film of the present invention is preferably a PET film with excellent physical and mechanical properties and a use temperature of up to 120°C.

[0035] According to some preferred embodiments, the composite method adopts a pressing and winding method; during the pressing and winding process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is controlled to be 0.5 to 2.5 m / s.

[0036] The present invention controls the winding tension and winding speed in the composite process of the support membrane and the porous polymer membrane within the above range, which can ensure that the porous polymer membrane and the support membrane are better composited without damaging the support membrane.

[0037] According to some preferred embodiments, the sulfonate is one or more of aminoalkyl sulfonate, sodium dodecylbenzene sulfonate, and biguanide trioctylbenzene sulfonate. The types of sulfonates of the present invention are not limited to the above range, and the above sulfonates are only for better explanation of the technical solution, not for limitation.

[0038] In order to form a hydrophilic coating on both sides of the porous base film by coating once and achieve the effect of double-sided hydrophilic coating, different requirements are set for the concentration of the hydrophilic coating slurry and the pore structure of the base film when selecting different sulfonates. Specifically, when the sulfonate is sodium dodecylbenzene sulfonate, the concentration of the hydrophilic coating slurry is 20-40% (sodium dodecylbenzene sulfonate accounts for 20-40wt% in the hydrophilic coating slurry), the pore size of the porous polymer film is 100-600nm, and the porosity is 35-40%. When the sulfonate is aminoalkyl sulfonate, the concentration of the hydrophilic coating slurry is 15-30% (aminoalkyl sulfonate accounts for 15-30wt% in the hydrophilic coating slurry), the pore size of the porous polymer film is 100-600nm, and the porosity is 35-40%. When the sulfonate is biguanide trioctylbenzene sulfonate, the concentration of the hydrophilic coating slurry is 30-40% (biguanide trioctylbenzene sulfonate accounts for 30-40wt% in the hydrophilic coating slurry), the pore size of the porous polymer membrane is 500-1500nm, and the porosity is 40-70%.

[0039] According to some preferred embodiments, the coating is performed by roller coating, and the winding tension of the support film is controlled to be 2.5-4kgf and the winding speed is 0.3-0.8m / s during the roller coating process. The present invention controls the winding tension and winding speed of the support film during the roller coating process to ensure that the hydrophilic coating slurry can fully penetrate to the other side of the porous base film and fill the pores, forming an effective double-sided hydrophilic coating and an efficient moisture permeable path. Under the same other conditions, if the winding speed is too large, the hydrophilic coating slurry will not be able to fully penetrate to the other side of the porous base film and fill the pores, resulting in poor moisture permeability and air tightness of the heat exchange membrane, and then the mildew resistance will decrease. If the winding speed is too small, although a double-sided hydrophilic coating can be formed, the efficiency is too low, and the efficiency improvement is not obvious compared to the double-sided coating method.

[0040] According to some preferred embodiments, the amount of the hydrophilic material used during the roller coating process is controlled to be 5 to 7 g / m 2 The present invention controls the amount of hydrophilic coating slurry and the coating speed (winding speed) during roller coating to ensure that the hydrophilic coating slurry can penetrate to the other side of the porous base membrane and fully fill the microporous structure of the base membrane, thereby obtaining a heat exchange membrane with excellent air tightness and moisture permeability.

[0041] According to some preferred embodiments, the drying temperature is 95-100° C. and the drying time is 50-60 seconds.

[0042] According to some preferred embodiments, after the drying, a release and winding step is also included; during the release and winding process, the winding tension of the support film is greater than the winding tension of the heat exchange film; preferably, the winding tension of the support film is 2.5 to 4 kgf, and the winding tension of the heat exchange film is 0.5 to 1 kgf; and / or

[0043] During the release and winding process, the support film and the heat exchange film have the same winding speed; preferably, the support film and the heat exchange film have a winding speed of 0.5-1 m / s.

[0044] The present invention separates the support film and the heat exchange membrane by release winding after drying. During the winding process, the winding tension of the support film is controlled to be greater than the winding tension of the heat exchange membrane. The winding speeds of the support film and the heat exchange membrane are the same to ensure that the support film and the heat exchange membrane are separated without damaging the two.

[0045] In a second aspect, the present invention further provides a heat exchange membrane with high-efficiency moisture permeability, which is prepared by the preparation method described in the first aspect.

[0046] The present invention further provides, in a third aspect, an application of the heat exchange membrane with high-efficiency moisture permeability as described in the second aspect, for use in a total heat exchange core.

[0047] The heat exchange membrane provided by the present invention has good air tightness, efficient moisture permeability and excellent mildew resistance, and can meet the use requirements of the high moisture permeability and air tightness of the heat exchange membrane for the efficient heat exchange full heat exchange core.

[0048] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0049] Example 1

[0050] The support film (PET film) and the porous base film (porous PE film, thickness of 18 μm, pore size of 100 nm, porosity of 35%) were compounded by pressing and rolling; wherein, the rolling tension of the support film during the pressing and rolling process was 2.5 kgf, and the rolling speed was 0.5 m / s;

[0051] The surface of the composite porous base film is roll-coated with a hydrophilic coating slurry (prepared by dissolving sodium dodecylbenzene sulfonate in water, wherein the sodium dodecylbenzene sulfonate accounts for 20wt% of the hydrophilic coating slurry). During the roll-coating process, the winding tension of the support film is controlled to be 2.5kgf, the winding speed is 0.3m / s, and the amount of the hydrophilic material used during the roll-coating process is 7g / m 2; The composite membrane after roller coating of the hydrophilic coating slurry is dried, wherein the drying temperature is 100°C and the drying time is 50s; the dried composite membrane is released and rolled up, and during the release and rolling process, the rolling tension of the support membrane is 2.5kgf, and the rolling tension of the heat exchange membrane is 0.5kgf; the rolling speed of the support membrane and the heat exchange membrane is 1m / s, and a heat exchange membrane with high efficiency moisture permeability is obtained.

[0052] Example 2

[0053] The support film (PET film) and the porous base film (porous PE film, with a thickness of 18 μm, a pore size of 400 nm, and a porosity of 40%) were compounded by pressing and rolling to obtain a composite film; wherein the rolling tension of the support film during the pressing and rolling process was 2.5 kgf, and the rolling speed was 0.5 m / s;

[0054] The surface of the composite porous base film is roll-coated with a hydrophilic coating slurry (prepared by dissolving sodium dodecylbenzene sulfonate in water, wherein the sodium dodecylbenzene sulfonate accounts for 40wt% of the hydrophilic coating slurry). During the roll-coating process, the winding tension of the support film is controlled to be 2.5kgf, the winding speed is 0.3m / s, and the amount of the hydrophilic material (sodium dodecylbenzene sulfonate) used during the roll-coating process is 5g / m 2 ; The composite membrane after roller coating of the hydrophilic coating slurry is dried, wherein the drying temperature is 100°C and the drying time is 50s; the dried composite membrane is released and rolled up, and during the release and rolling process, the rolling tension of the support membrane is 2.5kgf, and the rolling tension of the heat exchange membrane is 0.5kgf; the rolling speed of the support membrane and the heat exchange membrane is 1m / s, and a heat exchange membrane with high efficiency moisture permeability is obtained.

[0055] Example 3

[0056] The support film (PET film) and the porous base film (porous PE film, with a thickness of 18 μm, a pore size of 600 nm, and a porosity of 40%) were compounded by pressing and rolling to obtain a composite film; wherein the rolling tension of the support film during the pressing and rolling process was 2.5 kgf, and the rolling speed was 0.5 m / s;

[0057] The surface of the composite porous base film is roll-coated with a hydrophilic coating slurry (obtained by dissolving aminoalkyl sulfonate in water, wherein the aminoalkyl sulfonate accounts for 30 wt % of the hydrophilic coating slurry). During the roll-coating process, the winding tension of the support film is controlled to be 2.5 kgf, the winding speed is 0.3 m / s, and the amount of the hydrophilic material (aminoalkyl sulfonate) used during the roll-coating process is 6 g / m 2; The composite membrane after roller coating of the hydrophilic coating slurry is dried, wherein the drying temperature is 100°C and the drying time is 50s; the dried composite membrane is released and rolled up, and during the release and rolling process, the rolling tension of the support membrane is 2.5kgf, and the rolling tension of the heat exchange membrane is 0.5kgf; the rolling speed of the support membrane and the heat exchange membrane is 1m / s, and a heat exchange membrane with high efficiency moisture permeability is obtained.

[0058] Example 4

[0059] The support film (PET film) and the porous base film (porous PE film, with a thickness of 18 μm, a pore size of 1500 nm, and a porosity of 70%) were compounded by pressing and rolling to obtain a composite film; wherein the rolling tension of the support film during the pressing and rolling process was 2.5 kgf, and the rolling speed was 0.5 m / s;

[0060] The surface of the composite porous base film is roll-coated with a hydrophilic coating slurry (obtained by dissolving biguanide tri-octylbenzene sulfonate in water, wherein the biguanide tri-octylbenzene sulfonate accounts for 40 wt % of the hydrophilic coating slurry). During the roll-coating process, the winding tension of the support film is controlled to be 2.5 kgf, the winding speed is 0.8 m / s, and the amount of the hydrophilic material (biguanide tri-octylbenzene sulfonate) used during the roll-coating process is 7 g / m 2 ; The composite membrane after roller coating of the hydrophilic coating slurry is dried, wherein the drying temperature is 100°C and the drying time is 50s; the dried composite membrane is released and rolled up, and during the release and rolling process, the rolling tension of the support membrane is 2.5kgf, and the rolling tension of the heat exchange membrane is 0.5kgf; the rolling speed of the support membrane and the heat exchange membrane is 1m / s, and a heat exchange membrane with high efficiency moisture permeability is obtained.

[0061] Example 5

[0062] It is basically the same as Example 2, except that the porous base membrane is a porous PTFE membrane (with a thickness of 18 μm, a pore size of 400 nm, and a porosity of 40%).

[0063] Example 6

[0064] It is basically the same as Example 2, except that the porous base membrane is a porous PVDF membrane (with a thickness of 18 μm, a pore size of 400 nm, and a porosity of 40%).

[0065] Example 7

[0066] It is basically the same as Example 2, except that the porous base membrane is a porous PP membrane (thickness is 18 μm, pore size is 400 nm, and porosity is 40%).

[0067] Comparative Example 1

[0068] It is basically the same as Example 2, except that the porous base membrane is a porous PE membrane (pore diameter is 50 nm, porosity is 20%).

[0069] Comparative Example 2

[0070] It is basically the same as Example 2, except that the porous base membrane is a porous PE membrane (pore size is 2000 nm, porosity is 80%).

[0071] Comparative Example 3

[0072] It is basically the same as Example 2, except that sodium dodecylbenzene sulfonate accounts for 5wt% of the hydrophilic coating slurry.

[0073] Comparative Example 4

[0074] It is basically the same as Example 2, except that sodium dodecylbenzene sulfonate accounts for 50wt% of the hydrophilic coating slurry.

[0075] Comparative Example 5

[0076] It is basically the same as Example 2, except that the winding speed of the support film during the roller coating process is 1.5 m / s.

[0077] Comparative Example 6

[0078] It is basically the same as Example 2, except that the porous base membrane is not composited with the support membrane during the roller coating process.

[0079] The experimental results show that the thermal shrinkage rate of the porous base membrane (porous PE membrane) during the drying process of the uncompounded support membrane is too high (the thermal shrinkage rate is 25%), and the mechanical strength of the porous base membrane (porous PE membrane) is insufficient, which makes it impossible to roll up and coat the slurry.

[0080] Comparative Example 7

[0081] It is basically the same as Example 5, except that there is no supporting film during the roller coating process.

[0082] The experimental results show that the thermal shrinkage rate of the porous base membrane (porous PTFE membrane) during the drying process of the uncompounded support membrane is too high (the thermal shrinkage rate is 12%), and the mechanical strength of the porous base membrane (porous PTFE membrane) is insufficient, which makes it impossible to roll up and coat the slurry.

[0083] Comparative Example 8

[0084] It is basically the same as Example 6, except that there is no supporting film during the roller coating process.

[0085] The experimental results show that although the porous base membrane (porous PVDF membrane) has good temperature resistance (heat shrinkage rate is only 5%), the porous base membrane (porous PVDF membrane) itself has insufficient mechanical strength, which makes it impossible to roll up and apply slurry.

[0086] Comparative Example 9

[0087] It is basically the same as Example 7, except that there is no supporting film during the roller coating process.

[0088] The experimental results show that the thermal shrinkage rate of the porous base membrane (porous PP membrane) during the drying process of the uncompounded support membrane is too high (the thermal shrinkage rate is 70%), and the mechanical strength of the porous base membrane (porous PP membrane) is insufficient, which makes it impossible to roll up and coat the slurry.

[0089] The performance data of the heat exchange membranes prepared in various embodiments of the present invention and comparative examples are shown in Table 1, and the test method is as follows:

[0090] Thermal shrinkage: The test method refers to GB / T 17313-1998 "Thermal shrinkage test method", the test temperature is usually 90°C and the test time is 1h.

[0091] Air tightness: The test method refers to GB / T 1038-2000 "Plastic film and sheet gas permeability test method pressure difference method": This standard specifies the method of measuring the gas permeability of plastic film and sheet by pressure difference method.

[0092] Water vapor permeability: The test method refers to GB / T 1037-2021 Plastic film and sheet water vapor permeability test cup weight gain and weight loss method and GB / T 17146-2015 Building materials and their products water vapor permeability test method.

[0093] Mildew resistance level: At a temperature of 25℃~30℃ and a relative humidity of not less than 85%, seal the film on a culture dish. After 28 days of culture, observe its surface under a magnifying glass to see if there is any mold penetration. Usually, the implementation standard for mildew resistance testing of building materials is GB / T 1741-2007.

[0094] Table 1. Performance data of heat exchange membranes of the present invention and comparative examples

[0095]

[0096] It should be noted that the differences in air tightness and moisture permeability of Examples 1-4 are due to the differences in the pore structure of the base film, the type, concentration and amount of the hydrophilic material. The differences in moisture permeability between Example 2 and Examples 5-7 are mainly determined by the moisture permeability of the PTFE membrane, PVDF membrane and PP membrane itself.

[0097] The present invention tests the moisture permeability of the porous base membranes of Example 2 and Examples 5-7, and the moisture permeability is no more than 4.5 g / (m 2 ·h). As shown in Table 1, the heat exchange membrane provided by the present invention has good air tightness (not less than -0.09MPa), high moisture permeability (moisture permeability not less than 5.9g / (m 2 h)) and excellent mildew resistance (mildew resistance level 0), which is significantly better than porous base membranes and can meet the requirements of high moisture permeability and air tightness for heat exchange membranes in high-efficiency heat exchange full heat exchange cores.

[0098] Compared with Example 2, in Comparative Example 1, the pore size and porosity of the porous base membrane are too small, and the hydrophilic coating slurry cannot fully penetrate to the other side of the porous base membrane, resulting in poor moisture permeability and air tightness of the heat exchange membrane. In Comparative Example 2, the pore size and porosity of the porous base membrane are too large, and the hydrophilic material cannot effectively fill the pores, resulting in poor air tightness of the heat exchange membrane. At the same time, because an efficient moisture permeability path cannot be formed, the moisture permeability is poor, and the mildew resistance is reduced. In Comparative Example 3, because the concentration of the hydrophilic coating slurry is too low, the hydrophilic coating slurry can penetrate to the other side of the porous base membrane, but because the content of the hydrophilic material is too low, an effective double-sided hydrophilic coating cannot be formed and the pores cannot be fully filled, resulting in poor moisture permeability and air tightness of the heat exchange membrane, and thus the mildew resistance is reduced. In Comparative Example 4, due to the high concentration of the hydrophilic coating slurry, the hydrophilic material molecules will form aggregates or micellar structures, blocking the pores of the base membrane, resulting in the slurry being unable to penetrate to the other side of the porous base membrane, and failing to form a uniform hydrophilic coating on both sides of the porous base membrane at one time, resulting in poor moisture permeability and air tightness of the heat exchange membrane, and thus poor mildew resistance. In Comparative Example 5, due to the excessively fast winding speed, the slurry was unable to fully penetrate to the other side of the porous base membrane and fill the pores, and failed to form an effective double-sided hydrophilic coating, resulting in poor moisture permeability and air tightness of the heat exchange membrane, and thus poor mildew resistance.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a heat exchange membrane with high efficiency moisture permeability, characterized in that: The preparation method comprises: Compounding the support membrane with a porous base membrane; the porous base membrane is a porous polymer membrane, the pore size of the porous polymer membrane is 100 to 1500 nm, and the porosity is 35 to 70%; A hydrophilic coating slurry is coated on one side of the porous base membrane, and after drying, a hydrophilic coating is formed on both sides of the porous base membrane to obtain a heat exchange membrane with high efficiency moisture permeability; the hydrophilic material in the hydrophilic coating slurry accounts for 15-40wt%; the hydrophilic material is sulfonate.

2. The preparation method according to claim 1, characterized in that: The porous polymer membrane is one of a porous PE membrane, a porous PTFE membrane, a porous PVDF membrane, and a porous PP membrane; and / or The use temperature of the support film is greater than 100° C., and the support film is preferably a PET film.

3. The preparation method according to claim 1, characterized in that: The composite method adopts a pressing and winding method; during the pressing and winding process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is controlled to be 0.5 to 2.5 m / s.

4. The preparation method according to claim 1, characterized in that: The sulfonate is one or more of aminoalkyl sulfonate, sodium dodecylbenzene sulfonate, and biguanide trioctylbenzene sulfonate.

5. The preparation method according to claim 1, characterized in that: The coating is carried out by roller coating, and during the roller coating process, the winding tension of the support film is controlled to be 2.5-4 kgf, and the winding speed is controlled to be 0.3-0.8 m / s.

6. The preparation method according to claim 5, characterized in that: During the roller coating process, the amount of the hydrophilic material is controlled to be 5 to 7 g / m 2 .

7. The preparation method according to claim 1, characterized in that: The drying temperature is 95-100° C. and the drying time is 50-60 seconds.

8. The preparation method according to claim 1, characterized in that: After the drying, the method further comprises the step of releasing and rolling up; During the release winding process, the winding tension of the support film is greater than the winding tension of the heat exchange film; preferably, the winding tension of the support film is 2.5-4kgf, and the winding tension of the heat exchange film is 0.5-1kgf; and / or During the release and winding process, the support film and the heat exchange film have the same winding speed; preferably, the support film and the heat exchange film have a winding speed of 0.5-1 m / s.

9. A heat exchange membrane with high efficiency moisture permeability, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the heat exchange membrane with high efficiency moisture permeability according to claim 9, characterized in that: Used for full heat exchange core.

Citation Information

Patent Citations

  • Intelligent humidity-control barrier film and preparation method and application thereof

    CN110302947A

  • Preparation method of washable total heat exchange fresh air membrane

    CN116672906A

  • Moisture-permeable film for total heat exchange element, and total heat exchange element

    CN116940797A

  • Manufacturing method of moisture permeable film for total heat exchange element

    JP2022156537A

  • Polymer composite materials for building air conditioning or dehumidification and preparation method thereof

    KR1020120067210A